Animal physiology - Hill, Richard W.; Cavanaugh, Daniel; Anderson, Margaret 1941- (New York, NY Sinauer Associates, an imprint of Oxford University Press, 2022)
"Comprehensive, contemporary, and engaging, Animal Physiology provides evolutionary and ecological context to help students make connections across all levels of physiological scale."-- Provided by publisher.
Animals and environments : function on the ecological stage -- Molecules and cells in animal physiology -- Genomics, proteomics, and related approaches to physiology -- Physiological development and epigenetics -- Transport of solutes and water -- Nutrition, feeding, and digestion -- Energy metabolism -- Aerobic and anaerobic forms of metabolism -- The energetics of aerobic activity -- Thermal relations -- Food, energy, and temperature at work : the lives of mammals in frigid places -- Neurons -- Synapses -- Sensory processes -- Nervous system organization and biological clocks -- Endocrine and neuroendocrine physiology -- Reproduction -- Integrating systems at work : animal navigation -- Control of movement : the motor bases of animal behavior -- Muscle -- Movement and muscle at work : plasticity in response to use and disuse -- Introduction to oxygen and carbon dioxide physiology -- External respiration : the physiology of breathing -- Transport of oxygen and carbon dioxide in body fluids (with an introduction to acid-base physiology) -- Circulation -- Oxygen, carbon dioxide, and internal transport at work : diving by marine mammals -- Water and salt physiology : introduction and mechanisms -- Water and salt physiology of animals in their environments -- Kidneys and excretion (with notes on nitrogen excretion) -- Water, salts, and excretion at work : mammals of deserts and dry savannas.
Revised edition of: Animal physiology / Richard W. Hill, Gordon A. Wyse, Margaret Anderson. Fourth edition. ©2016.
Includes bibliographical references and index.
Keywords: Physiology, Comparative